Ultrasound scanning of the pelvis and abdomen for staging of gynecological tumors: a review - Fischerova, D (Ultrasound in obstetrics & gynecology, 2011)
This Review documents examination techniques, sonographic features and clinical considerations in ultrasound assessment of gynecological tumors. The methodology of gynecological cancer staging, including assessment of local tumor extent, lymph nodes and distant metastases, is described. With increased technical quality, sonography has become an accurate staging method for early and advanced gynecological tumors. Other complementary imaging techniques, such as computed tomography and magnetic resonance imaging, can be used as an adjunct to ultrasound in specific cases, but are not essential to tumor staging if sonography is performed by a specialist in gynecological oncology. Ultrasound is established as the method of choice for evaluating local extent of endometrial cancer and is the most important imaging method for the differential diagnosis of benign and malignant ovarian tumors. Ultrasound can be used to detect early as well as locally advanced cancers that extend from the vagina, cervix or other locations to the paracolpium, parametria, rectum and sigmoid colon, urinary bladder and other adjacent organs or structures. In cases of ureteric involvement, ultrasound is also helpful in locating the site of obstruction. Furthermore, it is specific for the detection of extrapelvic tumor spread to the abdominal cavity in the form of parietal or visceral carcinomatosis, omental and/or mesenteric infiltration. Ultrasound can be used to assess changes in infiltrated lymph nodes, including demonstration of characteristic sonomorphologic and vascular patterns. Vascular patterns are particularly well visualized in peripheral nodes using high resolution linear array probes or in the pelvis using high-frequency probes. The presence of peripheral or mixed vascularity or displacement of vessels seems to be the sole criterion in the diagnosis of metastatic or lymphomatous nodes. In the investigation of distant metastases, if a normal visceral organ or characteristic diffuse or focal lesions (such as a simple cyst, hepatic hemangioma, renal angiomyolipoma, fatty liver (steatosis)) are identified on ultrasound, additional examinations using complementary imaging methods are not required. If, however, less characteristic findings are encountered, especially when the examination result radically affects subsequent therapeutic management, an additional examination using a complementary imaging method (e.g. contrast-enhanced ultrasound, computed tomography, magnetic resonance imaging, positron emission tomography) is indicated.
Keywords: Ultrasonography; Ovarian Neoplasms; Neoplasm Staging; Abdomen; Genital Neoplasms, Female; pánev; nádory vaječníků; Endometrial Neoplasms; Lymphatic Metastasis; nádory ženských pohlavních orgánů; lidé; ženské pohlaví; Humans; Pelvis; lymfatické metastázy; Female; Vagina; vagina; staging nádorů; nádory endometria; ultrasonografie; břicho